Irony comprehension in first-degree relatives of patients with bipolar affective disorder – a preliminary fMRI study - Hajnal, András Sándor; Varga, Eszter; Tényi, Tamás; Pethő, Borbála; Albert, Noémi; Herold, Márton; Kovács, Márton Áron; Csulak, Tímea; Hebling, Dóra; Herold, Róbert (Frontiers in Psychiatry, 2025)
IntroductionMentalization or Theory of Mind (ToM) is crucial for interpreting social situations and understanding others’ beliefs and intentions. Irony comprehension, which involves constructing a coherent narrative from contradictory information, is linked to ToM. This study examines first-degree relatives of individuals diagnosed with bipolar I disorder to determine if irony comprehension and its neural correlates can serve as endophenotypic markers for bipolar disorder.MethodsThe study recruited 16 biological first-degree relatives of individuals diagnosed with bipolar I disorder (Relative Group, RG) and 16 healthy controls (Control Group, CG). Participants underwent an irony comprehension task under three conditions: irony (I), irony with linguistic assistance (IH), and control (C). Functional magnetic resonance imaging (fMRI) was employed to elucidate brain activation patterns during task execution.ResultsBehavioral analysis revealed no significant differences in task performance between RG and CG across all conditions. However, fMRI results demonstrated distinct neural activation patterns between groups during the statement phase of the tasks. The RG exhibited reduced activation in the temporoparietal junction, posterior cingulate cortex, thalamus, and cerebellum compared to CG in the I>IH contrast. Conversely, RG individuals exhibited enhanced activation in these regions during the IH>I and IH>C contrasts.DiscussionFirst-degree relatives of bipolar patients showed altered brain activity patterns during irony comprehension tasks, despite comparable behavioral performance. The observed neural patterns could indicate alternative cognitive strategies or latent vulnerability markers, underscoring the need for further multimodal investigation. Altered neural activation during irony processing may serve as an endophenotypic marker for bipolar disorder. Future research should explore these findings in larger cohorts and assess additional cognitive factors.